Internacionalização do ensino superior : o movimento na licenciatura em Química da Universidade Federal de Mato Grosso - Paula, Poliana Conceição Rocha de (2020)
The internationalization movement in higher education institutions has grown in size, purpose and complexity, reflecting a world with increasingly globalized and internationalized universities. With this advance of internationalization, challenges and opportunities for higher education institutions, especially the public ones, emerge, which point to the need to search for methods that favor the expansion of their borders, seeking partnerships and agreements with international institutions, aiming at strengthening actions of teaching, research and extension. In order to expand the studies on the internationalization movement of higher education in undergraduate courses, this work has as main focus to investigate the internationalization movement in the Licentiate Degree in Chemistry at the Federal University of Mato Grosso. It is a qualitative research directed to the case study. Multiple data sources were used to build the case in depth. Information pertinent to documents, interviews and archival records were analyzed, which allowed us to understand aspects related to the dynamics of internationalization actions in undergraduate courses and how this movement occurs. Although already inserted in a context of international cooperation since its early years, and especially in the structuring of its first laboratories, the data showed that the participation of the Chemistry Degree course, Cuiabá‟s campus, is very incipient in the internationalization movement of the Federal University Mato Grosso, mainly in the field of education.